Investments of the Military Accommodation Fund in the Context of Building a Modern State: Architecture, Ideology and Social Space of the Second Polish Republic - Rudnicka-Bogusz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article examines the Military Accommodation Fund (FKW) as a centrally managed investment and construction system operating in the Second Polish Republic in the interwar period. It analyses the Fund`s role in the standardization of residential and institutional buildings for the Polish Army between 1927 and 1937. Drawing on official reports and contemporary architectural sources, the article situates the Fund?s investments within broader state-led modernization processes.
Keywords: Military Accommodation Fund; Second Polish Republic; FKW; authoritarian state; spatial ideology; Sanacja; standardisation